Analisis Total Quality Service Terhadap Kepuasan Mahasiswa Universitas Kutai Kartanegara Tenggarong - Johansyah Johansyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
This research do analysis of the relationship among Tangibles Service Quality(X1), Reliability (X2),Responsiveness (X3) Assurance (X4), Empaty (X5) with satisfaction (Y) students in University of KutaiKartanegara. The research object is treated to the University of Kutai Kartanegara with all ofstudents from the whole faculties in University of Kutai kartanegara as respondents. According toanalysis result which is done, It’s gotten the regression equation Y=4,334 - 0,097X1 - 0,022X1X2 - 0,195X3 - 0,132X4 + 0,258X5